Long-run factors of firm growth - a study of German firms - Antje Schimke; Thomas Brenner (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
This paper investigates whether the economic factors that are related to firm growth in the literature also determine the development path of firms. This means that we test which economic factors possess the ability to remain effective for a longer period of time. We examine three variables: firm size, innovation effort and export share. To this end, we use panel-data on 178 German manufacturing firms over the period from 1992 to 2007. We find that the determinants of permanent growth path are not the same as the determinants of firm growth at one point in time.
urn:nbn:de:swb:90-228098
Keywords: 330; firm growth; firm growth paths; firm size; export; innovation effort